A major locus on chromosome 3p22 conferring predisposition to human herpesvirus 8 infection - Pedergnana, Vincent; Gessain, Antoine; Tortevoye, Patricia; Byun, Minji; Bacq-Daian, Delphine; Boland, Anne; Casanova, Jean-Laurent; Abel, Laurent; Plancoulaine, Sabine (European journal of human genetics : EJHG, 2012)
Infection with human herpesvirus 8 (HHV-8), the etiological agent of Kaposi's sarcoma, has been shown to display strong familial aggregation, in countries in which HHV-8 infection is endemic. We investigated 40 large families (608 subjects aged one to 88 years) living in an isolated area of Cameroon in which HHV-8 is highly endemic. We performed a two-step genetic analysis for HHV-8 infection status (HHV-8+/HHV-8- determined by immunofluorescence) consisting of an initial segregation analysis followed by a model-based genome-wide linkage analysis. Overall HHV-8 seroprevalence was 60%, increasing with age. Segregation analysis provided strong evidence for a recessive major gene conferring predisposition to HHV-8 infection. This gene is predicted to have a major effect during childhood, with almost all homozygous predisposed subjects (∼7% of the population) becoming infected by the age of 10. Linkage analysis was carried out on the 15 most informative families, corresponding to 205 genotyped subjects. A single region on chromosome 3p22 was significantly linked to HHV-8 infection (LOD score=3.83, P=2.0 × 10(-5)). This study provides the first evidence that HHV-8 infection in children in endemic areas has a strong genetic basis involving at least one recessive major locus on chromosome 3p22.